Characterizing crystal disorder of trospium chloride: a comprehensive,(13) C CP/MAS NMR, DSC, FTIR, and XRPD study - Urbanova, Martina; Sturcova, Adriana; Brus, Jiri; Benes, Hynek; Skorepova, Eliska; Kratochvil, Bohumil; Cejka, Jan; Sedenkova, Ivana; Kobera, Libor; Policianova, Olivia; Sturc, Antonin (Journal of pharmaceutical sciences, 2013)
Analysis of C cross-polarization magic angle spinning (CP/MAS) nuclear magnetic resonance (NMR), differential scanning calorimetry (DSC), Fourier transform infrared (FTIR), and X-ray powder diffraction data of trospium chloride (TCl) products crystallized from different mixtures of water-ethanol [φ(EtOH) = 0.5-1.0] at various temperatures (0°C, 20°C) and initial concentrations (saturated solution, 30%-50% excess of solvent) revealed extensive structural variability of TCl. Although (13) C CP/MAS NMR spectra indicated broad variety of structural phases arising from molecular disorder, temperature-modulated DSC identified presence of two distinct components in the products. FTIR spectra revealed alterations in the hydrogen bonding network (ionic hydrogen bond formation), whereas the X-ray diffraction reflected unchanged unit cell parameters. These results were explained by a two-component character of TCl products in which a dominant polymorphic form is accompanied by partly separated nanocrystalline domains of a secondary phase that does not provide clear Bragg reflections. These phases slightly differ in the degree of molecular disorder, in the quality of crystal lattice and hydrogen bonding network. It is also demonstrated that, for the quality control of such complex products, (13) C CP/MAS NMR spectroscopy combined with factor analysis (FA) can satisfactorily be used for categorizing the individual samples: FA of (13) C CP/MAS NMR spectra found clear relationships between the extent of molecular disorder and crystallization conditions. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1235-1248, 2013.
Keywords: Crystallization; Benzilates; Nortropanes; krystalizace; benziláty; Calorimetry, Differential Scanning; Magnetic Resonance Spectroscopy; spektroskopie infračervená s Fourierovou transformací; Powder Diffraction; Spectroscopy, Fourier Transform Infrared; magnetická rezonanční spektroskopie; diferenciální skenovací kalorimetrie; difrakce rentgenového záření; X-Ray Diffraction; prášková difrakce; nortropany